1990
DOI: 10.1002/bjs.1800770705
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns of incidence and mortality from acute pancreatitis in Scotland, 1961–1985

Abstract: Data on all discharges from hospitals in Scotland have been recorded since 1961 as the Scottish Hospital In-Patient Statistics and examination of these data has permitted analysis of the incidence and mortality trends from acute pancreatitis. The number of discharges recorded has increased 11-fold in males from 69 patients/year in 1961 to 750 patients/year in 1985, and fourfold in females from 112 patients/year to 484 patients/year respectively. This increase has occurred particularly amongst young and middle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1
3

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 5 publications
4
42
1
3
Order By: Relevance
“…These data compare well with what has been presented in another Swedish study [3] where 10 out of 31 deaths due to acute pancreatitis (32%) were identified from the forensic department and the patients were not ever admitted to hospital. In patients admitted to hospital but with an overlooked diagnosis obtained first at autopsy, the incidence of missed diagnosis has been reported as high as 30-42% [4,5]. It seems that a minority of these patients had abdominal pain at admission and that amylase was infrequently determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data compare well with what has been presented in another Swedish study [3] where 10 out of 31 deaths due to acute pancreatitis (32%) were identified from the forensic department and the patients were not ever admitted to hospital. In patients admitted to hospital but with an overlooked diagnosis obtained first at autopsy, the incidence of missed diagnosis has been reported as high as 30-42% [4,5]. It seems that a minority of these patients had abdominal pain at admission and that amylase was infrequently determined.…”
Section: Discussionmentioning
confidence: 99%
“…As acute pancreatitis represents a frequent condition with reported yearly incidences of approximately 30 patients per 100,000 inhabitants per year [3,4], the mortality encountered in the disease also represents a quantitative problem. Thirty to forty percent of patients with fatal acute pancreatitis have been reported diagnosed first at autopsy [4,5,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Epidemiology: The true incidence of acute pancreatitis remains difficult to ascertain, primarily because of descriptive anomalies as previously stated, but also 21,22 There is evidence to suggest that the overall incidence is increasing and may reflect population changes in alcohol consumption and dietary habits. 23 A large epidemiological study involving 1068 cases from five countries in Europe over 4 years reported similar incidence and mortality rates between the participating countries, but found regional variations in the underlying causes. Alcohol was the most frequent aetiology in northern, and gallstones in southern countries.…”
Section: Acute Pancreatitismentioning
confidence: 97%
“…Twenty per cent of patients develop a severe attack with organ failure or other complications and there is an associated overall mortality rate of 7%. [3][4][5] The risk of recurrent GSP occurs in as many as 31% of patients within the first two weeks of discharge; however, this is reduced significantly with timely definitive surgical management or endoscopic treatment in those unfit for surgery. 6 The British Society of Gastroenter- prevent recurrence of symptoms.…”
mentioning
confidence: 99%